Effects of the Susceptor Dielectric Properties on the Microwave Sintering of Alumina. Issue 12 (13th November 2013) - Heuguet, Romain; Marinel, Sylvain; Thuault, Anthony; Badev, Alexandre; Reimanis, I.
<x xml:space="preserve">Abstract</x> Microwave sintering of alumina has been carried out using SiC and Y‐ZrO2 based susceptors. The microstructure of the sintered samples has been rigorously compared and correlated to the heating behaviour of the susceptor used. It was found that the nature of the susceptor highly influences the sintering behaviour of alumina. The results show that at high temperatures, the electrical conductivity of the SiC susceptor tends to screen the incident electric field, thus resulting in a surface heating of the alumina sample material. When using ZrO2 susceptor, the microstructure analysis of the sintered alumina samples reveals a volumetric heating, which is a signature of the microwave dielectric loss mechanism. This could be explained by the lower ZrO2 electrical conductivity compared to the SiC one. The simulation results confirm this behaviour, particularly showing that in the presence of ZrO2, the intensity of the electric field within the sample is higher than the one when SiC susceptor is used. Basically, the results of the simulation data are in good agreement with our experimental results. Although the SiC based susceptor is usually used in the microwave heating of materials, the ZrO2 based susceptor presents numerous advantages over the SiC one, especially in term of direct microwave heating contributions.